HISTORY OF SYNTAX STUDY IN KOREAN AND UZBEK LANGUAGES - Khayotkhon Zoitovna Kakhorova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This article is devoted to syntax and sentence types in Korean and Uzbek: simple and compound sentences, as well as sentence structure, sentences and their expression, and it discusses the history of syntax and sentence in Korean and Uzbek. The origin and description of simple and compound sentences in Korean and Uzbek are given. The history of syntax in both languages ​​shows the stages of its development and mentions the scientists who contributed to this development.